In vitro exposure to epididymal extracellular vesicles from normospermic domestic cats improves developmental potential of sperm from teratospermic cats - Sosnicki, Danielle M.; Travis, Alexander J.; Comizzoli, Pierre (Frontiers in Veterinary Science, 2025)
We have previously reported a difference in the composition of epididymal extracellular vesicles (EVs) between normospermic and teratospermic domestic cats. The objective of the present study was to investigate whether the fertilizing ability or developmental potential of sperm from teratospermic cats could be improved after incubation with EVs isolated from normospermic cats. For each of 11 experimental replicates, pools of EVs were collected from the whole epididymides of 5 normospermic cats (normospermic EVs). Spermatozoa were also collected from the cauda epididymides of 2 teratospermic cats, pooled, and half was co-incubated with normospermic EVs for 1 h and 15 min prior to using the sperm for in vitro fertilization (IVF). The other half of the sperm was kept for 1 h and 15 min in the absence of EVs as a control group. We found no difference (p > 0.05) in sperm fertilizing ability, based on the percentage of cleaved embryos, after incubation with EVs (67.0%) and without EVs (60.6%). However, the developmental potential of teratospermic sperm, based on the proportion of embryos that reached the 8-cell stage or further, was better (p < 0.05) after co-incubation with EVs (58.4%) compared to the control group without EVs (47.2%). Additionally, the proportion of embryos that reached the blastocyst stage was better (p < 0.05) after co-incubation with EVs (30.7%) compared to the control group without EVs (19.9%). These findings can be used to improve the outcome of IVF with teratospermic males in domestic or wild felid species.